El debate en torno al 'argumento del intellectus essentiae' y la 'distinción real' entre la esencia y el ser en el 'De ente et essentia' de Tomás de Aquino - Ocampo, Fernanda (2018)
The so-called 'intellectus essentiae argument' has constituted one of the resources of some 13th century authors, to establish the 'real distinction' between essence and being in every creature. This argument is also present in Aquinas' De Ente et Essentia, a work in which, the philosopher is believed to have tried to demonstrate the 'real distinction or composition' as well. Now, it is precisely the meaning and scope of this argument regarding the demonstration of the 'real distinction' in Thomas' argumentation that has been object of recent debate among specialists. In this sense, we intend in this article to first expose the argument in the context of the work to which it belongs, then concentrate on the opinions of the different commentators, and finally outline our conclusions based on the interpretations we consider the most accurate.